EVALUASI SISTEM PENGENDALIAN INTERNAL TERHADAP SIKLUS PEMBELIAN BAHAN BAKU PADA PT. XYZ - Didi, Didi; Hestiany, Efin; Afif , M. Nur (Komunitas Manajemen Kompetitif, 2025)
This study aims to evaluate the internal control system over the raw material purchasing cycle at PT. XYZ, using the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework. The research method includes observation, questionnaires, and document analysis to assess the five components of internal control, as well as strategy formulation using the TOWS analysis. The results show that, overall, the internal control system operates fairly well, supported by a clear organizational structure, documented standard operating procedures (SOPs), and the use of an ERP system. However, weaknesses remain in risk assessment, ERP integration with suppliers, and the accuracy of raw material requirement data. The implementation of internal control is relatively aligned with the COSO framework, particularly in control environment and monitoring components, though risk assessment, control activities, and communication require strengthening. The strategy to enhance internal control effectiveness focuses on the Opportunities-Strengths (OS) quadrant of the TOWS matrix, leveraging internal strengths and external opportunities through technology optimization, employee training, and improved procedures and interdepartmental communication. Keywords: internal control system, raw material purchasing, COSO, TOWS